2015
DOI: 10.1016/j.livsci.2015.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory expression of components in the BMP pathway in white adipose tissues of cattle

Abstract: a b s t r a c tThe BMP pathway positively regulates murine brown adipogenesis. We herein examined the mRNA levels of BMPs and activin βB as well as receptors for the BMP pathway in the adipose tissues of cattle fed diets with a differential ratio of concentrate to roughage or a vitamin A-deficient diet. The expression of activin βB was significantly increased in the subcutaneous fat depot of animals fed the concentrate diet, while the vitamin A-deficient diet significantly increased the expression of BMP4 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…The present study indicated that the vitamin A restriction significantly increased or tended to increase expression of Bmp7 and Bmpr2 in both fat depots, Alk3 and Actr2a in scWAT, and Alk2 in mesWAT. The results are partly consistent with the results of a study using TMR as described previously (Qiao et al, 2015); feeding the vitamin A-restricted diet significantly increased or tended to increase expression of Bmp4, ActβB, Alk2, Alk3, Actr2a, and Bmpr2 in mesWAT. The current study also showed that expression levels of Alk3 in scWAT were positively correlated with those of transcriptional regulators other than Zfp516 to induce brown/beige adipogenesis in scWAT.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study indicated that the vitamin A restriction significantly increased or tended to increase expression of Bmp7 and Bmpr2 in both fat depots, Alk3 and Actr2a in scWAT, and Alk2 in mesWAT. The results are partly consistent with the results of a study using TMR as described previously (Qiao et al, 2015); feeding the vitamin A-restricted diet significantly increased or tended to increase expression of Bmp4, ActβB, Alk2, Alk3, Actr2a, and Bmpr2 in mesWAT. The current study also showed that expression levels of Alk3 in scWAT were positively correlated with those of transcriptional regulators other than Zfp516 to induce brown/beige adipogenesis in scWAT.…”
Section: Discussionsupporting
confidence: 91%
“…The cDNA that was reverse-transcribed from 5, 10, or 20 ng of total RNA was used as a template for reverse transcription-quantitative PCR (RT-qPCR) as described previously (Kanamori et al, 2017). The oligonucleotide primers for cell death-inducing DFFA-like effector a (Cidea), cytochrome c oxidase (Cox) 7a, Cox8b, iodothyronine deiodinase 2 (Dio2), hypoxanthine phosphoribosyltransferase 1 (Hprt1), Pgc-1α, Prdm16, and Ucp1 were described in the study by Asano et al (2013), and those for activin βB (ActβB), activin receptor type 2a (Actr2a), activin receptor-like kinase (Alk) 2, Alk3, bone morphogenetic protein (Bmp) 4, Bmp7, and Bmp receptor type 2 (Bmpr2) were described previously (Qiao et al, 2015). The other PCR primers are shown in Table 2.…”
Section: Rna Isolation and Reverse Transcription-quantitative Pcrmentioning
confidence: 99%